Understanding the effects of ion and neutron irradiation on tungsten - Abernethy, R (2018)
Tungsten will be an important material inside future fusion reactors. However, replicating the neutron irradiation that it will be exposed to in that environment is currently impractical. As a result ion irradiation is being used to extend the dose and temperature range. Irradiation hardening data from past experiments show a discrepancy between the results of these two irradiation species. This work involves the first direct comparison between ion irradiation and neutron irradiation of tungsten, carried out at fusion relevant temperatures to a dose of 1.6 dpa. The materials from these irradiations have been examined to investigate the induced microstructural changes. Irradiation hardening measurements were carried out using nanoindentation and a model applied to correlate this with the defects observed. This has provided critical insight into neutron irradiation induced hardening at fusion relevant temperatures and shown that the discrepancy between ion and neutron irradiation hardening can be significantly reduced by accounting for the effect of transmutation. The change in brittle to ductile transition (BDT) caused by neutron irradiation of single crystal tungsten has been fully characterised. These results show that the BDT temperature has increased by 500 K, yet activation energy has remained constant at 1.0 eV and activation volume at 5 b3, strongly suggesting that the controlling mechanism remains kink-pair nucleation of screw dislocations. Investigations into the BDT in polycrystalline tungsten have shown anomalous strain rate dependence, with micro-cantilever testing showing grain boundary embrittlement. Micro-pillar compression has also been applied to the ion irradiated W and W-1.4Re in order to acquire additional mechanical properties from ion irradiation experiments. Results from this experiment have shown that strain burst behaviour is strongly enhanced by ion irradiation of W-1.4Re, indicating that irradiation induced rhenium precipitation is changing dislocation behaviour. By comparison, displacement damage caused by ion irradiation of pure W appear to have a small effect on micropillar deformation.